Pharmacokinetic Profile of a Generic Formulation of Sofosbuvir and Its Metabolite GS‐331007 in Healthy Chinese Subjects. Issue 8 (22nd March 2019) - Shen, Zhenwei; Zhu, Xiaoxue; Zhang, Hong; Chen, Hong; Niu, Junqi; Chen, Guiling; Li, Xiaojiao; Ding, Yanhua
Abstract: Sofosbuvir is an NS5B nucleotide inhibitor for the treatment of hepatitis C viral infection. In this study the pharmacokinetics (PK) and safety of single and multiple doses of generic sofosbuvir were investigated in healthy Chinese subjects. Twelve subjects (6 male and 6 female) were enrolled in this study. The PK parameters of sofosbuvir and its metabolite (GS‐331007) in both blood and urine samples were analyzed after dosing by the established liquid chromatography tandem mass spectrometry analytical method. The safety/tolerability assessment consisted of documenting adverse events, vital signs, electrocardiogram, and laboratory test results. Sofosbuvir was well tolerated. Major PK parameters of the generic formulation of sofosbuvir were similar to those found in previous reports. These data support further clinical evaluation of this generic formulation of sofosbuvir.